2014
DOI: 10.1371/journal.pone.0111556
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Transcription in a Distal Region Upstream from the Bovine AlphaS1 Casein Gene after Once or Twice Daily Milking

Abstract: Once daily milking (ODM) induces a reduction in milk production when compared to twice daily milking (TDM). Unilateral ODM of one udder half and TDM of the other half, enables the study of underlying mechanisms independently of inter-individual variability (same genetic background) and of environmental factors. Our results show that in first-calf heifers three CpG, located 10 kb upstream from the CSN1S1 gene were methylated to 33, 34 and 28%, respectively, after TDM but these levels were higher after ODM, 38, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 63 publications
3
25
0
Order By: Relevance
“…For instance, earlier it was observed that the promoter region of rat Csn3 is hypomethylated in lactating mammary tissue, but it is hypermethylated in nonmammary tissues and nonlactating mammary tissue (223). Similar effects were observed in primiparous dairy cows where CpG islands upstream of the CSN1S1 gene were methylated to 55 and 71% on average for mammary gland and liver, respectively, during pregnancy (159). Decreased percentage of methylation of the same CpG islands upstream of the CSN1S1 was observed from once to twice daily milking (36 vs. 32%, respectively), which was accompanied by an increase in expression of CSN1S1 and an increase in daily milk protein.…”
Section: Epigenetic Regulation Of Milk Synthesissupporting
confidence: 70%
See 1 more Smart Citation
“…For instance, earlier it was observed that the promoter region of rat Csn3 is hypomethylated in lactating mammary tissue, but it is hypermethylated in nonmammary tissues and nonlactating mammary tissue (223). Similar effects were observed in primiparous dairy cows where CpG islands upstream of the CSN1S1 gene were methylated to 55 and 71% on average for mammary gland and liver, respectively, during pregnancy (159). Decreased percentage of methylation of the same CpG islands upstream of the CSN1S1 was observed from once to twice daily milking (36 vs. 32%, respectively), which was accompanied by an increase in expression of CSN1S1 and an increase in daily milk protein.…”
Section: Epigenetic Regulation Of Milk Synthesissupporting
confidence: 70%
“…Deletion of STAT5 in the mammary gland of mouse compromised the expression of whey acidic proteins and lactalbumin but had no effects on beta casein (Csn2) (178). Although these data indicate that STAT5 might not be necessary to the basal expression of Csn2, others have reported a significant and numerical decrease in Csn2 expression under both reduced phosphorylation and increased methylation of the binding site for STAT5 (49,159). Overall, there exists substantial evidence that STAT5 plays a central role in mammary gland development and function by interacting with several signaling pathways controlling milk protein gene expression and cell survival (50,83).…”
Section: Transcription Factors Controlling Expression Of Casein Genesmentioning
confidence: 87%
“…A separate report has shown that rat kappa-casein (CSN3) promoter region is hypomethylated in lactating mammary tissue, but hypermethylated in non-mammary tissues and non-lactating mammary tissue [97]. A similar effect was observed in primiparous dairy cows wherein their CpG islands upstream of CSN1S1 (α-casein S1) gene were methylated 55% and 71% on average in mammary gland and liver, respectively, during pregnancy [95,98]. After parturition, the methylation percentage of the same CpG islands in the upstream of CSN1S1 gene was decreased from one to two times of daily milking (36 vs. 32%, respectively).…”
Section: Epigenetic Regulation Of Milk Synthesismentioning
confidence: 91%
“…This area of DNA contains three CpG islands near the binding sites of signal transducer and activator of transcription 5 (STAT5), a transcription factor involved in signal transduction of the hormone prolactin (Vanselow et al, 2006). In the mammary gland, these CpG sites are less methylated (<30%) during lactation than during puberty, gestation or involution (between 35% and 60%), while being hypermethylated in the liver (>65%; Vanselow et al, 2006;Singh et al, 2012;Nguyen et al, 2014). The high level of DNA methylation at these three CpG sites during mammary involution was associated with a low expression of the CSN1S1 gene (Singh et al, 2012).…”
Section: S53mentioning
confidence: 99%
“…During differential milking, the milk yield of the half-udder milked 1 × was lower than its contralateral half-udder milked 2 × . This reduction in milk yield was associated with greater CpG methylation levels upstream of the CSN1S1 gene and a lower RNA level of this gene in the 1 × -milked half-udder than in the 2 × -milked half-udder (Nguyen et al, 2014). In contrast, a severe and long-term feed restriction during early lactation in dairy cows did not affect the levels of CSN1S1 mRNA and CpG methylation upstream of this gene (Boutinaud et al, 2016).…”
Section: Effect Of Challenges On Epigenetic Marksmentioning
confidence: 99%